Septicemia asociada a catéter venoso central - Ramírez Cardoce, Manuel (2012)
The use of central venous catheters (CVC) isvery common in national hospitals, because theyimprove the care of critically ill patients as wellas the administration of irritant drugs likechemotherapy, parenteral nutrition and someantibiotics and specific parenteral solutions.They are also used to perform medical proce-dures as plasmaferesis and hemofiltration. Be-cause of its location in the deep venous system,they are very important sites of ingress for path-ogens. This review describes the main types ofCVC, the sources and sites of infection and therisk factors linked to CVC-associated septicemia.It also describes the recommendations for CVCsubstitution and the most frequent bacterial florafound as cause of infection.